2012
DOI: 10.1111/j.1524-475x.2012.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous and exogenous enzymes in chronic wounds: A focus on the implications of aberrant levels of both host and bacterial proteases in wound healing

Abstract: Cutaneous wound healing is orchestrated by a number of physiological pathways that ultimately lead to reformation of skin integrity and the production of functional scar tissue. The remodeling of a wound is significantly affected by matrix metalloproteinases (MMPs), which act to control the degradation of the extracellular matrix (ECM). Regulation of MMPs is imperative for wound healing as excessive levels of MMPs can lead to disproportionate destruction of the wound ECM compared to ECM deposition. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 116 publications
(157 reference statements)
3
106
1
2
Order By: Relevance
“…3,33 Studies have shown that chronic wound fluid contains elevated protease levels known to have deleterious effects, such as the degradation of de novo granulation tissue and endogenous biologically active proteins such as growth factors and cytokines. 34,35 Protease-lowering dressings have demonstrated efficacy at removing slough, promoting granulation tissue formation, and stimulating wound repair. CHOOSING THE CORRECT WOUND DRESSING 37 An example of a protease-lowering dressing is the phosphorylated cotton wound dressings prepared to target sequestration of proteases from chronic wound exudate through a cationic uptake binding mechanism involving salt bridge formation of the positively charged amino acid side chains of proteases with the phosphate counter-ions of the wound dressing fiber.…”
Section: Fibrinous Wound Beds (Slough)mentioning
confidence: 99%
“…3,33 Studies have shown that chronic wound fluid contains elevated protease levels known to have deleterious effects, such as the degradation of de novo granulation tissue and endogenous biologically active proteins such as growth factors and cytokines. 34,35 Protease-lowering dressings have demonstrated efficacy at removing slough, promoting granulation tissue formation, and stimulating wound repair. CHOOSING THE CORRECT WOUND DRESSING 37 An example of a protease-lowering dressing is the phosphorylated cotton wound dressings prepared to target sequestration of proteases from chronic wound exudate through a cationic uptake binding mechanism involving salt bridge formation of the positively charged amino acid side chains of proteases with the phosphate counter-ions of the wound dressing fiber.…”
Section: Fibrinous Wound Beds (Slough)mentioning
confidence: 99%
“…3,26 Protease activity is essential for cutaneous wound healing, as demonstrated by the retarded wound healing seen in mice deficient in plasminogen, the serine protease precursor, and mice treated with a metalloprotease inhibitor. 9 Neutrophil elastase has also demonstrated antimicrobial properties against a range of wound-associated bacteria.…”
mentioning
confidence: 99%
“…Excessive inflammation due to the persistence of a critical bacterial contamination, biofilm or infection leads to wound chronicity [4]. Stalling of ulcer healing, which do not progress beyond the inflammatory phase, has been related to persistent inflammation [5] and an increase of matrix metalloproteases and elastase activities [6,7] . .…”
Section: Discussionmentioning
confidence: 99%